2020
DOI: 10.21125/iceri.2020.0752
|View full text |Cite
|
Sign up to set email alerts
|

Student Perspectives on the Covid-19 Emergency Remote Teaching at a Catalan Engineering School

Abstract: Due to the COVID-19 health crisis, the UPF closed its physical doors in mid-March, in line with all other universities. As a result, all teaching activities (initially conceived as on-site) had to be reorganised in order to fit a new, totally online learning environment. The Teaching Quality and Innovation Support Unit (USQUID) at the UPF Engineering School and ICT Department has provided the students and teachers of the School with support and guidance in many ways, including devising a feedback questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Considering that, the literature shows mixed results regarding the changes in the measured satisfaction around the pandemic years. Some studies have reported that satisfaction during the pandemic was not significantly impacted for the worse in countries used to online or mixed learning (Abdull Mutalib et al, 2022;Moreno Oliver & Hernández-Leo, 2020;Montero et al, 2020). Conversely, students with limited resources and lack of connectivity and living in remote or rural areas reported being unsatisfied with the changes towards online education (Aristovnik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that, the literature shows mixed results regarding the changes in the measured satisfaction around the pandemic years. Some studies have reported that satisfaction during the pandemic was not significantly impacted for the worse in countries used to online or mixed learning (Abdull Mutalib et al, 2022;Moreno Oliver & Hernández-Leo, 2020;Montero et al, 2020). Conversely, students with limited resources and lack of connectivity and living in remote or rural areas reported being unsatisfied with the changes towards online education (Aristovnik et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The transition between these teaching modalities, from in-person to online and mixed learning, was often too quick and sometimes hard for educators because of the lack of preparation for several HEIs (Beardsley et al, 2021;Busuttil & Camilleri, 2020;Martin et al, 2022;Sahu, 2020). Studies about the impact of this emergency change of teaching modality showed that students reported being more satisfied with the courses that took advantage of real-time conferences, video recordings, presentations and written tasks, in that order, for their development (Aristovnik et al, 2020;Moreno Oliver & Hernández-Leo, 2020). However, there is still room for more studies describing the effects on student satisfaction caused by the changes in teaching modalities at the institutional level (Scaringella et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The design of learning activities and programs must be pedagogically sound in terms of their quality (Caridade, 2020;Hodges et al, 2020;Quezada et al, 2020;Serrano-Arcos et al, 2020;World Bank, 2020) and flexibility (Caridade, 2020;Daniel, 2020;Moreno Oliver & Hernández-Leo, 2020;Quezada et al, 2020). C. Multi-modal and varied resources are to be put in place by institutions to support and foster such educational modalities, both for educators and students (Ali, 2020;Daniel, 2020;de Trazegnies Otero & Vargas Domínguez, 2020;García Alberti et al, 2020;Moreno Oliver & Hernández-Leo, 2020;Mosquera Feijoo et al, 2020;Williamson et al, 2020;World Bank, 2020).…”
Section: Lessons Learnt From Ertmentioning
confidence: 99%
“…B.Techno-pedagogical training is required by educators to be able to respond to the educational context(Adedoyin & Soykan, 2020;Berkling, 2020;Hodges et al, 2020;Moreno Oliver & Hernández-Leo, 2020;Prieto- Jiménez et al, 2021;Serrano-Arcos et al, 2020).…”
mentioning
confidence: 99%